Hydroxytriazenes as Metallochromic Indicators for Complexometric Determination of Ion in Complexometric Determination of Iron in Pharmaceutical Preparations - Jain, C.P.; Chauhan, R.S.; Goswami, A.K.; Purohit, D.N. (Asian Journal of Chemistry, 2010)
The present paper deals with complexometric determination of Fe(III) using two hydroxytriazines as metallochromic indicators in two medicines Rubraplex (Sarabhai, India) and Fesovit (SKF, India) respectively. The hydroxytriazines used are 3-hydroxy-3-methyl-1-m-nitrophenyltriazine and 3-hydroxy-3-ethyl-1-p- nitrophenyltriazine.